1993
DOI: 10.1172/jci116329
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Marburg virus in human endothelial cells. A possible mechanism for the development of viral hemorrhagic disease.

Abstract: Marburg and Ebola

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 24 publications
2
71
0
Order By: Relevance
“…Several cell lines (E6, MA 104 and Vero), which do not express the ASGP-R, support replication of MBG. Furthermore, MBG is able to infect human endothelial cells which also lack the ASGP-R (Schnittler et al, 1993). For this reason it has to be postulated that, in addition to the ASGP-R, other receptors may mediate entry of MBG into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several cell lines (E6, MA 104 and Vero), which do not express the ASGP-R, support replication of MBG. Furthermore, MBG is able to infect human endothelial cells which also lack the ASGP-R (Schnittler et al, 1993). For this reason it has to be postulated that, in addition to the ASGP-R, other receptors may mediate entry of MBG into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (1998) suggested that EBO infection of endothelial cells may cause the hemorrhagic diapedesis in guinea pigs. Studies showing infection of endothelial cells by MBG and EBO viruses in vitro (Geisbert and Jaax, 1998;Schnittler et al, 1993) and filovirusinfected endothelial cells in postmortem tissues from humans and nonhuman primates (Baskerville et al, 1985;Davis et al, 1997;Geisbert et al, 1992;Jaax et al, 1996;Zaki and Goldsmith, 1999) have been used to support these views. More recent studies employing serially collected rodent and monkey tissues show that endothelial cell infection is, in fact, primarily associated with later stages of infection (Connolly et al, 1999;Ryabchikova et al, 1999).…”
Section: Geisbert Et Almentioning
confidence: 99%
“…Unlike the filoviruses, Marburg and Ebola, that destroy vascular endothelial cells in culture [Schnittler et al, 1993;Feldmann et al, 1996;Yang et al, 1998;Baize et al, 1999], arenaviruses like Lassa fever virus do not destroy cultured endothelial cells, but do diminish their capacity to express chemokines [Fisher-Hoch et al, 1987;Schnittler et al, 1993;Lukashevich et al, 1999]. Also unlike Ebola and Marburg hemorrhagic disease, Lassa fever disease does not cause an increase in fibrinogen breakdown products or diffuse intravascular coagulation (DIC) [Fisher-Hoch et al, 1988].…”
Section: Subclinical Transient Mucosal Infection Of Rhesus Macaques Bmentioning
confidence: 99%